Custos por aluno de graduação levantados no período de 2009 a 2016, no Centro de Ciências Agrárias, Campus II da UFPB - Machado, Andréia Maria de Oliveira (2020)
Knowing and analyzing costs per student is extremely relevant in public institutions of higher education, as allows to understand how public resources are being applied. In this perspective, the general objective of this research was to measure the cost per undergraduate student based on the expansion policy implemented by REUNI at the Center for Agricultural Sciences, Campus II of UFPB in the period from 2009 to 2016. The measurement of cost per student generates control mechanisms that can be used, in order to seek greater operational efficiency as well as to promote conditions for improving quality in expenses. In order to achieve the objectives, set, a qualitative research was carried out, with a bibliographic and documentary character, and analysis of quantitative data. All data related to current expenses for Campus II, received by the National Treasury, from 2009 to 2016, were collected, characterizing the research universe. This is a case study, as it consists of an in-depth research of one unit, the CCA/UFPB. The methodology applied was that of MEC/SESu to obtain the cost per student. The theoretical framework is based on some approaches to Higher Education and the aspects highlighted in the federal public administration are as follows: budget, public budget, budget composition, costs in the Public Sector, costs of public education in Brazil, the Federal Government-SIC Information System, propose methodologies for calculating education cost, cost systems and costing methods. Base on Technical Note 04/2018, the results of the research revealed that UFPB Campus II presented values lower than the national average regarding the average annual cost per student at federal universities and also institutionally. Therefore, it was found in the analyzed period that the resource allocation model, coordinated by the sectors of Campus I, harmed Campus II in relation to the annual cost of students, since there was a reduction proportional to the national average and, above all, to the average of UFPB.